Economic Costs of Delayed Diagnosis of Functional Motor Disorders: Preliminary Results From a Cohort of Patients of a Specialized Clinic - Michele Tinazzi; Marialuisa Gandolfi; Stefano Landi; Chiara Leardini (Frontiers in Neurology, 2021)
Background: Functional motor disorders (FMDs) are prevalent and highly disabling conditions in young adults that can result in reduced independence. Despite advances in diagnosis and treatment, the economic burden of FMDs is largely unknown.Objective: This pilot retrospective study provides a real-world overview of the economic costs related to delayed diagnosis of FMDs from a cohort of patients of a specialized clinic in Italy, based on Italian healthcare costs.Methods: Sociodemographic data, clinical history, healthcare service utilization, and associated direct costs were collected for a period of up to 5 years before a definite diagnosis of FMDs in 40 patients.Results: The mean time lag between the onset of FMDs symptoms and diagnosis was 6.63 years (±8.57). The mean annual use of recourses per patient was three specialist visits (95% CI 2.4–3.4) and three diagnostic examinations (95% CI 2.2–3.6) that made up a total of six investigations and over seven (95% CI 5.5–9.7) rehabilitation contacts per year per patient were used before a diagnosis of FMDs was established. In more than 50% of the cases, patients had been hospitalized or made an ER visit at least once before receiving the correct diagnosis. The average annual costs for delayed diagnosis, taking into account only direct healthcare costs (without medications), was about €2,302 (CI 95% €1,570–2,830) per patient [€1,524 covered by the NHS (CI 95% €1,214–1,834) and € 778 by the patient (CI 95% €606–960)]. Hospitalization accounted for €916 (CI 95% €670–1,160) per patient per year, followed by rehabilitation €493 (CI 95% €345–641) and diagnostic tests € 387 (CI 95% €314–460).Conclusion: These preliminary results shed some light on the high healthcare services volume and direct healthcare costs from clinic to clinic for visits, unnecessary tests, and prescribed treatments in a real-world overview from a cohort of patients of a specialized clinic in Italy. It may represent a starting point for future studies to statistically test and quantify cost reduction after implementing appropriate healthcare pathways.